PETROLOGY OF HIGH PRESSURE METAMORPHIC ROCKS FROM LUK ULO MELANGE COMPLEX, KARANGSAMBUNG, CENTRAL JAVA-INDONESIA - -, Aton Patonah; -, Haryadi; -, Bambang Priadi (Fakultas Teknik Geologi Universitas Padjadjaran, 2009)
Luk Ulo Melange Complex is situated in Central Java, this complex is characterized by the occurrence of Tertiary and Pre-Tertiary rocks as fragments embedded in sheared clay matrix. The fragments consist of ophiolite, metamorphic, chert and carbonate rocks. This research is focused to high pressure metamorphic rock which is represented by glaucophane schist. The rocks consists of albite, augite and ferroaugite, Mg – cataphorite, glaucophane, ferrian and crossite, almandine spesartine, quartz; and rarely can be observed lawsonite, hornblende, tremolite and actinolite. The latter mineral assemblage indicates that the rock was formed at 580oC - 500oC and 14,5 - 4 kbar. Temperature and pressure obtained from glaucophane schist indicated that the rock came from the lower interval of the subduction environment and the possibility have already been in retrograde stage. This is showed by recrystallization of amphibole-glaucophane to sericite or chlorite, and chlorite after garnet. This may represent the retrograde stage in lower temperature-pressure conditions. This data explains the accretion and exhumation history of high pressure metamorphic rocks from subduction depth to the surface condition.